2016
DOI: 10.1021/jacs.6b03293
|View full text |Cite
|
Sign up to set email alerts
|

An Alkali Metal-Capped Cerium(IV) Imido Complex

Abstract: Structurally authenticated, terminal lanthanide-ligand multiple bonds are rare and expected to be highly reactive. Even capped with an alkali metal cation, poor orbital energy matching and overlap of metal and ligand valence orbitals should result in strong charge polarization within such bonds. We expand on a new strategy for isolating terminal lanthanide-ligand multiple bonds using cerium(IV) complexes. In the current case, our tailored tris(hydroxylaminato) ligand framework, TriNOx(3-), provides steric prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 38 publications
6
73
1
1
Order By: Relevance
“…As with the  NLMO compositions, the other QTAIM metrics for the analogous U and Ce systems are very similar to one another, and indicate a significantly covalent M-O interaction, with  and H values amongst the largest (in an absolute sense) seen for f element bonds. Indeed, the present  and H are approximately double the value of the equivalent metrics of the M(IV)-C multiple bonds recently reported by Liddle et al 17 Pleasingly, the covalency trend Ce ≈ U > Th is the same in both our system and the BIPM TMS compounds.…”
supporting
confidence: 79%
“…As with the  NLMO compositions, the other QTAIM metrics for the analogous U and Ce systems are very similar to one another, and indicate a significantly covalent M-O interaction, with  and H values amongst the largest (in an absolute sense) seen for f element bonds. Indeed, the present  and H are approximately double the value of the equivalent metrics of the M(IV)-C multiple bonds recently reported by Liddle et al 17 Pleasingly, the covalency trend Ce ≈ U > Th is the same in both our system and the BIPM TMS compounds.…”
supporting
confidence: 79%
“…Recently, we reported the isolation of the first Ce IV terminal oxo complex [(L OEt ) 2 Ce(=O)(H 2 O)] ⋅ MeC(O)NH 2 ( 1 ; L OEt − =[Co(η 5 ‐C 5 H 5 ){P(O)(OEt) 2 } 3 ] − ) (Scheme ) . This major breakthrough in cerium chemistry has been rapidly developed by excellent contributions from others, for example, in the synthesis of the first cerium(IV)–imido complexes . The initial reactivity studies of the oxocerium complex 1 are intriguing in their variation: we have found both a classical 1,2‐insertion without change of the Ce oxidation state ([2π+2π]‐type metathesis) and reductive insertion (Scheme ) .…”
Section: Methodsmentioning
confidence: 99%
“…In these compounds, the steric properties of the amide and imido ligands determinedt he overall geometry of the compounds. In compounds 2 and 3,t he imido ligand was the mosts terically demanding, which causedt he N = U-N amide bond angle to be largea tt he expense of decreasing the (5), U(1)ÀN(4) 1.960 (5), N(4)ÀC(19) 1.486 (7),C (19)-N(4)-U(1) 179.3 (4), N(4)-U(1)-N(1) 113.13 (19), N(1)-U(1)-N(2) 105.33(17);3-U(1)ÀN(1) 2.269(6), U(1)ÀN(2) 1.956 (9), N(2)ÀC(7) 1.502 (14), C(7)-N(2)-U(1) 180.000 (2), N(2)-U(1)-N(1) 115.23 (15), N(1)-U(1)-N(1) 103.15(18);4-U(1)ÀN(1) 1.9503 (14), U(1)ÀN(2) 2.2313 (14), U(1)ÀN(3) 2.2529 (14), U(1)ÀN(4) 2.2469 (14), N(1)ÀC(1) 1.387(2), C(1)-N(1)-U(1)172.32 (13), N(1)-U(1)-N(2) 99.51, N(2)-U(1)-N(3) 115.42 (5). N amide -U-N amide bond angles and lengthening the UÀN amide bonds.…”
Section: Synthesis Of Uranium Mono(naphthylimido) Complexesmentioning
confidence: 99%
“…This increase in bond polarization often results in relatively more reactive multiply‐bonded compounds. Recent efforts in this area have resulted in the first example of cerium–nitrogen and cerium–oxygen multiple bonds . However, relativistic effects dictate that uranium has more chemically active 6d and 5f orbitals, which leads to increased orbital overlap and covalency in U−E multiple bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation